ASSOCIATION OF CD4 LEVELS WITH FLUCONAZOLE RESISTANCE IN HIV / AIDS PATIENTS WITH OROPHARYNGEAL CANDIDIASIS AT HAJI ADAM MALIK GENERAL HOSPITAL MEDAN - Olga Yanti Hutapea, Rahimi A, Ginting F & Dian D (International Journal of Research Science and Management, 2020)
Oropharingeal candidiasis is clinically characterized by decline of CD4. The standard treatment for oropharingeal candidiasis by CDC 2009 recommendation is fluconazole. Treatment with fluconazole often develops failure of therapy, high relapse and incidence in HIV / AIDS patients.The aim of this study was toinvestigate the association of CD4 levels with fluconazole resistance in HIV / AIDS patients with oropharingeal candidiasis in RS.H. Adam Malik. The crosssectional approach on 36 HIV / AIDS patients with oropharingeal candidiasis in January-August 2017. Patients who fulfilled inclusion criteria were examined CD4 and candida sensitivity test. Data analysis using Fisher Exact Test and Mann-Whitney U test. The level of fluconazole resistance to CD4 was 19.4% and fluconazole resistance to C.albicans was 8%, while for C.non albicans the level of resistance to fluconazole was 45%. The candid a sensitivity test results on fluconazole did not have significant differences (p> 0.05) and there was a significant difference in CD4 levels with the type of candida species. There was no association of CD4 levels with sensitivity test results and there was association between the type of fungus with the sensitivity test results. There was a significant difference in CD4 levels with the type of candida species.